High-resistivity unintentionally carbon-doped GaN layers with nitrogen as nucleation layer carrier gas grown by metal-organic chemical vapor deposition - Fu Chen; Shichuang Sun; Xuguang Deng; Kai Fu; Guohao Yu; Liang Song; Ronghui Hao; Yaming Fan; Yong Cai; Baoshun Zhang (AIP Advances, 2017)
In this letter, high-resistivity unintentionally carbon-doped GaN layers with sheet resistivity greater than 106 Ω/□ have been grown on c-plane sapphire substrates by metal-organic chemical vapor deposition (MOCVD). We have observed that the growth of GaN nucleation layers (NLs) under N2 ambient leads to a large full width at half maximum (FWHM) of (102) X-ray diffraction (XRD) line in the rocking curve about 1576 arc sec. Unintentional carbon incorporation can be observed in the secondary ion mass spectroscopy (SIMS) measurements. The results demonstrate the self-compensation mechanism is attributed to the increased density of edge-type threading dislocations and carbon impurities. The AlGaN/GaN HEMT grown on the high-resistivity GaN template has also been fabricated, exhibiting a maximum drain current of 478 mA/mm, a peak transconductance of 60.0 mS/mm, an ON/OFF ratio of 0.96×108 and a breakdown voltage of 621 V.